ITS sequences from nuclear rDNA suggest unexpected phylogenetic relationships between Euro-Mediterranean, East Asiatic and North American taxa ofQuercus ( (Plant systematics and …, 1998)
Nucleotide sequences from the internal transcribed spacer (ITS) regions of the 18S-26S nuclear ribosomal DNA have been studied from ten species of Quercus (representing four subgenera), Castanea sativa and Fagus sylvatica, as a preliminary molecular contribution to the still poorly understood systematics and evolution of Fagaceae. The resulting matrix has been used to calculate pair-wise sequence divergence indices and to construct a maximum parsimony tree for Quercus coding indels as a fifth state. Divergence is greater for Quercus vs. Fagus than for Quercus vs. Castanea. The tree for the Quercus taxa studied reveals two clearly divergent clades. In clade I the evergreen W Mediterranean Q. suber appears in a basal position as sister to more distal deciduous taxa, i.e. the E Mediterranean Q. macrolepis and the E Asiatic Q. acutissima (all formerly united as different sections under the apparently polyphyletic subg. Cerris), and Q. rubra (a representative of the N American subg. Erythrobalanus), forming a pair with Q. acutissima. In clade II the evergreen southeastem N American Q. virginiana is basal and sister to the remaining three branches, i.e. a pair of evergreen Mediterranean taxa with Q. ilex and Q. coccifera (subg. Sclerophyllodrys), the deciduous but otherwise plesiomorphic SE European/SW Asiatic Q. cerris (type species of subg. Cerris), and the related but more apomorphic European pair Q. petraea and Q. robur (subg. Quercus). These results partly conflict with current taxonomic classification but a_re supported by some anatomical and morphological characters. They document polyphyletic lines from evergreen to deciduous taxa and suggest Tertiary transcontinental connections within the genus.